2016
DOI: 10.1109/tmi.2016.2578939
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Detection Using Composite Impedance Metric

Abstract: Prostate cancer (PCa) recurrences are often predicted by assessing the status of surgical margins (SM) – positive surgical margins (PSM) increase the chances of biochemical recurrence by 2–4 times which may lead to PCa recurrence. To this end, an electrical impedance acquisition system with a microendoscopic probe was employed in an ex-vivo study of human prostates. This system measures the tissue bioimpedance over a range of frequencies (1 kHz to 1MHz), and computes a number of Composite Impedance Metrics (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
(47 reference statements)
0
28
0
1
Order By: Relevance
“…In comparison to our prior study (Khan et al 2016), the clinical parameters are quite similar, but here we have significantly improved registration between impedance measurements, yielding a more nuanced analysis on accuracy as a function of percent cancer. Overall, the results presented in this paper corroborate our previous studies and present the strongest evidence yet that an intraoperative-capable impedance probe can be used to distinguish benign from malignant prostate tissues.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In comparison to our prior study (Khan et al 2016), the clinical parameters are quite similar, but here we have significantly improved registration between impedance measurements, yielding a more nuanced analysis on accuracy as a function of percent cancer. Overall, the results presented in this paper corroborate our previous studies and present the strongest evidence yet that an intraoperative-capable impedance probe can be used to distinguish benign from malignant prostate tissues.…”
Section: Discussionmentioning
confidence: 76%
“…6/9 and 9/6) to give a total of 16 impedance measurements per ring. A noise filter applied to the data removes patterns whose 1) voltage difference is too small (< 50 mV), 2) voltage or current noise power is too large (> 2 V and > 3/(499 Ω) A for voltage and current, respectively; see (Khan et al 2016) for description of noise power measurements in this system and note that 499 Ω is the resistor used on the current sense electrode), and/or 3) if the sensed current magnitude is too small (< 0.1 mA, in voltage drive mode). These thresholds were empirically determined and were conservatively chosen to keep higher quality measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on BIA revealed enthusiastic results mainly in patients with aggressive cancers [5][6][7]. Studies conducted in the setting of prostate cancer in particular, were limited by the applicability of proper probes on the prostate gland surface and by the anatomic deep site in which the prostate is placed inside the pelvic bone girdle [8].…”
Section: Introductionmentioning
confidence: 99%